The Red Seal - Lincoln, Natalie Sumner, 1881-1935 (Salt Lake City, UT : Project Gutenberg, 1999)
"The Red Seal" by Natalie Sumner Lincoln is a mystery novel likely written during the early 20th century. The narrative begins in a police court, where the complex circumstances surrounding a case of house-breaking unfold, involving the unfortunate incident of James Turnbull, a bank cashier who dies under mysterious conditions. The story intricately weaves the lives of the McIntyre twins, particularly Helen and Barbara, as they grapple with the implications of Turnbull's death and a puzzling connection to their social circle. At the start of the book, the tension builds as the courtroom drama reveals character testimonies that lead to the arrest of a man named John Smith, who is implicated in the alleged house-breaking. As the proceedings unfold, Helen McIntyre, one of the twin daughters of a wealthy colonel, intimately witnesses the trial and the unraveling events. The narrative then shifts dramatically when a sudden heart attack befalls Turnbull, who is later discovered disguised as the burglar. The opening portion culminates in Helen's emotional confrontation with the repercussions of the tragedy, hinting at deeper themes of love, deception, and societal expectations. As the characters navigate through grief and suspicion, questions arise about Turnbull's true motives and the circumstances leading to his death, setting the stage for a thrilling exploration of intrigue and human emotions. (This is an automatically generated summary.)
Release date is 1999-05-01
Produced by An Anonymous Volunteer, and David Widger
Keywords: Fiction